Green Synthesis of New Category of Pyrano[3,2-c]Chromene-Diones Catalyzed by Nanocomposite as Fe3O4@SiO2-Propyl Covalented Dapsone-Copper Complex - Zare Fekri, Leila (Frontiers in Chemistry, 2021)
Nanomagnetic dapsone-Cu supported on silica coated Fe3O4 (Fe3O4@SiO2-pr@dapsone-Cu) nanocomposite was synthesized and characterized by FT-IR, EDX, XRD, FESEM, TEM, zeta potential, VSM and TGA. This new synthesized nanocomposite was chosen to act as a green, efficient and recyclable lewis acid for the multicomponent synthesis of new derivatives of pyrano[3,2-c] chromene-diones through the reaction of aromatic aldehydes, indandione and 4-hydroxycoumarin in water. All of synthesized compounds are new and were recognized by FT-IR, NMR and elemental analysis this avenue is new and has advantages as short reaction times, high productivity, economical synthesis and use of green solvent, H2O as medium. The catalyst is magnetically recoverable and can be used after six runs without decrease in the efficiency.